Economic growth and the issue of women participation in adult education - Dieter Dohmen; Galiya Yelubayeva (Forschungsinstitut für Bildungs- und Sozialökonomie (FiBS), 2019)
[Introduction] The necessity of growth support was embedded into the core message adopted by the European Commission in the Europe 2020 strategy, which recommends a number of structural reforms in order to boost labor utilization and productivity growth (European Commission, 2011). This article presents an in-depth appraisal of the theoretical approaches in relation to the link between adult education (human capital in general) disaggregated by gender and macroeconomic growth and a summary of results from the main empirical macro-studies for European countries. The literature on economic growth is vast and policy-oriented studies, in particular, have flourished in the past decade. Yet, there is little agreement on the exact mechanisms linking policy settings to growth. So far, we have not come across the studies modelling adult education variables into Human capital, and empirical investigations seeking to test its relation to macroeconomic indicators except FiBS/CEDEFOP study in 2012 (CEDEFOP, 2012). Human capital theory signifies the modern economy focused on the increasing role of human capital in the knowledge-based society. The human resources development is an important part of all development strategies and has recently been embodied in the policy and reports of most important international institutions: the European Commission and other regional policy institutions (Cedefop, 2011, 2016, 2017). The theoretical emphasis on human capital was laid mainly by endogenous growth theory, starting with Becker, who was probably the first ones who emphasized the role of human capital in technology adoption and its impact on economic growth. However the concept of human capital was fully embodied later, mainly in works of Romer (1986) and Lucas (1988) and Barro (1991) (Robert J Barro, 1991; Lucas, 1988; Romer, 1989). Generally, although, education and growth literature is largely based on the endogenous growth models, it is however, neglected human capital accumulation in stage of adult education and differences in gender impact. Needs to mention is that since each different scholar uses varied estimation methods and data, this has led to different conclusions, and therefore economic growth and human capital and gender issues remains a place worthy of study and discussion, which possesses distinct theoretical and practical significance. The paper deals with three issues: (1) whether gender inequality is present in further education participation (2) whether gender specific human capital and separately taken gender inequality index contributes to economic growth. Accordingly, the paper is structured as follows. The first section shows the review of studies on gender issues and education issues in relation to economic growth, then the second section explains methodological framework of the empirical model and data used. Then results of the empirical results and some policy implications and recommendations for further research are given in section four. We argue that there is a significant social loss if women do not revert to working force. The contribution makes a series of recommendations to rectify the participation gap.
Additional information: Study as part of the project "Economic and regional costs, funding structures and benefits of continuing education" (VoREFFI-WB) - Funded by the Federal Ministry of Education and Research.
Keywords: 330